1933 S.D. Sess. Laws 245-47, ch. 206, &sect - (:unkn) unknown (My University, 1933)
Prohibited possession of a machine gun during a violent crime. Punishable by imprisonment up to 15 years. Prohibited using a machine gun offensively or aggressively; punishable by imprisonment up to 15 years. Requires manufacturers to keep a register of machine guns and for owners to converted their machine guns to pistols to register the weapon.
&sect
1-8
Keywords: MACHINE GUN RESTRICTION